Inheritance and allelic relationship of white rust resistance gene in the crosses of exotic and indigenous germplasm lines of Indian mustard [Brassica juncea (L.) Czern. and Coss.]: INHERITANCE OF WHITE RUST RESISTANCE IN INDIAN MUSTARD - CHANDANA BEHERA; DEVENDRA K YADAVA; SUJATA VASUDEV; NAVEEN SINGH; NAVINDER SAINI; H D PUSHPA; M S YADAV; KUMBLE V PRABHU (Journal of Oilseeds Research, 2016)
White rust caused by Albugo candida (Pers. ex Lev.) Kuntze is a destructive disease in many important Brassica species including Brassica juncea in India. It leads to massive yield losses with maximumdamage upto 89.8 per cent under late sown conditions due to staghead formation. Identification of diverse sources ofresistance is a prerequisite for proper cost effective and eco-friendly management of white rust in Indian mustard. Here, a combination of both exotic and indigenous sources of B. juncea was taken to study the genetics of white rust resistance. Five resistant genotypes viz., BEC144, BEC286, EC399299, Heera and BioYSR were crossed to Bio 902 (Pusa Jaikisan) an otherwise high-yielding popular variety of Indian mustard but susceptible to white rust. The F1 s of the ten crosses including reciprocals were resistant indicating the dominance nature of white rust resistance in Indian mustard. Segregation of 3 resistant: 1 susceptible plants in F2 generation showed the monogenic inheritance of white rust resistance. Further, backcross generations revealed segregation of 1 resistant: 1 susceptible plants confirming that white rust resistance is governed by a single dominant gene which can easily be transferred through backcrossing froma resistant donor to high yielding, well adapted susceptible genotypes. Crosses among the resistant donors have also been attempted to study the allelic relationship among the five resistant sources; and F2 population of all possible twenty crosses including reciprocals showed complete resistance indicating the genes for white rust resistance in these resistant sources were allelic to each other.